Failure analysis of a diesel generator connecting rod. (October 2016) - Juarez, C.; Rumiche, F.; Rozas, A.; Cuisano, J.; Lean, P.
Highlights: A failure analysis investigation of a connecting rod was conducted. The origin of the fracture was located at the con-rod lubrication channel. The lubrication channel exhibited an area containing an embedded W-based material. W-based material acted as nucleation site for cracks that propagated by fatigue. Abstract: This paper presents the results of a failure analysis investigation conducted in a connecting rod from a diesel engine used in the generation of electrical energy. The investigation included an extensive analysis of the con-rod material as well as the fracture zone. The investigation involved the following experimental procedures and testing techniques: visual inspection, fractography, magnetic particle inspection, chemical analysis, tensile and hardness testing, metallography, and microanalysis. The connecting rod was fabricated from an AISI/SAE 4140 low alloy steel; chemical composition, mechanical properties and microstructure were appropriate for the application. The connecting rod fractured at the body in a section close to the head; the origin of the fracture was located at the con-rod lubrication channel. The lubrication channel exhibited an area containing a tungsten based material, presumably from a machining tool, embedded in its surface as a result of a deficient manufacturing process. This area acted as nucleation site for cracks that propagate through the connecting rod section by a fatigue mechanism, reducing its section and finally producing its catastrophic failure.